Digital government : technology and public sector performance - West, Darrell M., 1954- (Princeton University Press, 2007)
Few developments have had broader consequences for the public sector than the introduction of the Internet and digital technology. In this book, Darrell West discusses how new technology is altering governmental performance, the political process, and democracy itself by improving government responsiveness and increasing information available to citizens. Using multiple methods--case studies, content analysis of over 17,000 government Web sites, public and bureaucrat opinion survey data, an e-mail responsiveness test, budget data, and aggregate analysis--the author presents the most c.